=
Note: Conversion is based on the latest values and formulas.
How do you integrate (tanx)^2? - Socratic 21 Aug 2016 · We will use the Trigo. Identity # : sec^2x=tan^2x+1#.. Hence, #int(tanx)^2 dx=int tan^2xdx=int (sec^2x-1)dx# ...
Web 2.0 scientific calculator Free Online Scientific Notation Calculator. Solve advanced problems in Physics, Mathematics and Engineering. Math Expression Renderer, Plots, Unit Converter, Equation Solver, Complex Numbers, Calculation Histo
What is the square root of x squared? - Socratic 31 May 2015 · The term 'the square root of X' is not quite precise as there are usually 2 square roots called sqrt(X) and -sqrt(X) sqrt(x^2) = abs(x) This is the positive square root of x^2. -sqrt(x^2) = -abs(x) is also a square root of x^2 It's tempting to …
What is (lnx)^2? - Socratic 30 Jun 2017 · See below. f(x) = (lnx)^2 lnx is defined for x>0 hence, f(x) is defined x>0 lim_(x-> 0) f(x) = +oo and lim_(x->oo) f(x) =+oo f'(x) = 2lnx*(1/x) {Chain rule] For a ...
What is the derivative of tan^2 x? - Socratic 11 Oct 2017 · #"note "tan^2x=(tanx)^2# #"differentiate using the "color(blue)"chain rule"# #"given "y=f(g(x))" then"# #dy/dx=f'(g(x))xxg'(x)larr" chain rule"#
Is (lnx)^2 equivalent to ln^2 x? - Socratic 23 Sep 2017 · Yes, but also see below ln^2 x is simply another way of writing (lnx)^2 and so they are equivalent. However, these should not be confused with ln x^2 which is equal to 2lnx There is only one condition where ln^2 x = ln x^2 set out below. ln^2 x = ln x^2 -> (lnx)^2 = 2lnx :. lnx * lnx = 2lnx Since lnx !=0 lnx * cancel lnx = 2 * cancel lnx lnx = 2 x =e^2 Hence, ln^2 x = ln x^2 is …
How do you factor x^2 + x - 42? - x - 42? | Socratic 21 Sep 2015 · First, I thought of the factors of x^2. The only possible ones are x and x. Next, I thought: What two factors of -42 are equal to 1 (since that is the coefficient of x) when added? The two numbers that I thought of were -6 and 7, since -6+7=1. Therefore, my factors are (x+7) and (x-6). You can try double-checking this by multiplying (x+7) and ...
How do you write x^2+ 3x in factored form? - Socratic 15 Sep 2015 · x(x+3) x^2+3x x(x+3) How do you find the two numbers by using the factoring method, if one number is seven more than...
What does the graph cos^2(x) look like? - Socratic 19 Sep 2015 · Have a look: This is the same as the normal cos where the negative bits became positive because of the square: Graphically:
How do you factor x^2 - y^2 ? + Example - Socratic 7 Jul 2015 · This is known as a difference of squares. It can be factored as: x^2 - y^2 = (x-y)(x+y) Notice that when you multiply (x-y) by (x+y) then the terms in xy cancel out, leaving x^2-y^2 ... (x-y)(x+y) = x^2+xy-yx-y^2 = x^2+xy-xy-y^2 = x^2-y^2 In general, if you spot something in the form a^2-b^2 then it can be factored as (a-b)(a+b) For example: 9x^2-16y^2 = (3x)^2-(4y)^2 = (3x …